Seasonal changes in body iron status including erythropoiesis and hemolysis and dietary intakes among Japanese collegiate elite female rhythmic gymnasts - Kokubo, Y.; Yokoyama, Y.; Kotemori, A.; Kawano, Y. (The Journal of Physical Fitness and Sports Medicine, 2020)
Female rhythmic gymnasts with dietary problems are extremely conscious of their physical shape and often are diagnosed with iron deficiency (ID). Although there are several reports on training volume and quality throughout the year, there are few reports on the association between dietary intake and prevalence of ID. The aim of this study was to examine the association between the prevalence of ID, including erythropoiesis and hemolysis, and dietary intake for 10 months. A total of 19 Japanese collegiate elite female rhythmic gymnasts participated in five surveys in four different seasons: early pre-season (April), late pre-season (July and August), in-season (October), and off-season (January). Blood samples were collected to analyze body iron status including delta-aminolevulinic acid dehydratase (ALAD) activity, erythropoietin, and haptoglobin, and dietary intake were assessed. The definition of anemia was based on hemoglobin concentrations (<12.0 g/dL), and ID was diagnosed when one of the following clinical criteria or both were met: ferritin (< 12 ng/mL) and transferrin saturation (< 16 %). A higher incidence of ID (58%) was noted in July and August. ALAD was significantly higher in July to October than in April. Erythropoietin did not show any significant changes throughout the study. Haptoglobin was significantly lower in August than in January. Intakes of energy, protein, and iron were significantly lower in August than in April. Our findings suggest that inadequate intakes such as energy, protein and iron may concern with the high incidence of ID in August when the synthesis and destruction of red blood cells is enhanced in elite rhythmic gymnasts.